Ireland’s Specific Features and its Application of English Language Variabilities in the Spoken Language - Amir Abushaev (Scientific Trends, 2023)
Irish English, also known as Hiberno-English, has its roots in the Old and Middle English varieties spoken by Anglo-Norman settlers who arrived in Ireland during the late 12th and early 13th centuries. Over time, the language evolved due to interactions between these settlers and the native Irish-speaking population. Some key milestones in the development of Irish English include: The introduction of the Anglo-Norman language after the Norman invasion in 1169; The gradual decline of Gaelic as the dominant language, resulting in a shift to English-speaking communities; The establishment of a distinct Irish English dialect by the early 18th century; The impact of the Great Famine in the 19th century, leading to increased emigration and the spread of Irish English to other English-speaking countries.
Keywords: Famine, Irish accent, actualization, increasing popularity, variations, specific features, population, century, well-known.